2015
DOI: 10.1021/nl503745b
|View full text |Cite
|
Sign up to set email alerts
|

Edge-on Gating Effect in Molecular Wires

Abstract: This work demonstrates edge-on chemical gating effect in molecular wires utilizing the pyridinoparacyclophane (PC) moiety as the gate. Different substituents with varied electronic demands are attached to the gate to simulate the effect of varying gating voltages similar to that in field-effect transistor (FET). It was observed that the orbital energy level and charge carrier's tunneling barriers can be tuned by changing the gating group from strong electron acceptors to strong electron donors. The single mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 33 publications
2
65
0
2
Order By: Relevance
“…1a ). 17 In this system, we took the advantage of the perpendicular orientation between the two aromatic planes and used the pyridine end of the moiety as the gating part of the wire attached with functional groups of different electronic demands. 18 , 19 Further studies by the scanning tunneling microscopy break-junction (STM-BJ) technique demonstrated that the single-molecule conductance, the orbital energy level, and the charge tunneling barrier of these molecular wires can be tuned by changing the electronic properties of the gating substituent group.…”
Section: Introductionmentioning
confidence: 99%
“…1a ). 17 In this system, we took the advantage of the perpendicular orientation between the two aromatic planes and used the pyridine end of the moiety as the gating part of the wire attached with functional groups of different electronic demands. 18 , 19 Further studies by the scanning tunneling microscopy break-junction (STM-BJ) technique demonstrated that the single-molecule conductance, the orbital energy level, and the charge tunneling barrier of these molecular wires can be tuned by changing the electronic properties of the gating substituent group.…”
Section: Introductionmentioning
confidence: 99%
“…Diphenyl-pyridinoparacyclophane-diphenyl molecular transistor (Copyright 2015, American Chemical Society). [13] conductance values to those measuredp reviously for neutral molecules. The protonation described herem arkedlyi ncreased electron-withdrawinga bility of the pyridine gating unit and by extension switching the charge-transport channel from HOMO to the LUMO leadingt os ignificantly reduced conductance.…”
Section: Modulating Charge Transport Through Edge-on Gatingmentioning
confidence: 85%
“… Diphenyl–pyridinoparacyclophane–diphenyl molecular transistor (Copyright 2015, American Chemical Society) …”
Section: Modulating Charge Transport Through Edge‐on Gatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Одним из базовых элементов молекулярной наноэлек-троники является одномолекулярный транзистор, в ко-тором проводимость осуществляется через одиночную органическую молекулу (или малую группу таких мо-лекул) [2][3][4]. Ключевой проблемой в данных структурах является формирование наноразмерных контактов сто-ка и истока в совокупности с затворным электродом для возможности исследования полевого управления канала.…”
Section: Introductionunclassified